2023
DOI: 10.1007/s10639-023-11895-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital competence of teachers in the use of ICT for research work: development of an instrument from a PLS-SEM approach

Abstract: All spheres of our life are being affected using technology, particularly its integration in the research processes carried out by teachers. The success of the integration of specific digital resources in research work can be affected by several factors, such as: digital skills for finding information, managing it, analyzing it, and communicating results; digital flow; anxiety in the use of ICT; digital ethics; quality of digital resources; and finally, the behavioral intention to integrate ICT. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…1 was shown, the study built and analyzed a structural equation model, which revealed that ICT attitude, ICT skills, and data literacy had significant positive correlations on digital teaching competence. Previous studies constructed models, confirming some factors influencing teachers' digital teaching competence, such as attitude (Scherer et al 2019;Huang and Liaw, 2005), skills (Guillén-Gámez et al 2023;Kaarakainen et al 2018;Knezek and Christensen, 2016), gender, age (He et al 2023) and so on. Therefore, we focused on exploring the endogenous factors, including attitude and skills, combined with data literacy, which is rarely explored in prior studies but proven to be necessary for teachers.…”
Section: Discussionmentioning
confidence: 60%
“…1 was shown, the study built and analyzed a structural equation model, which revealed that ICT attitude, ICT skills, and data literacy had significant positive correlations on digital teaching competence. Previous studies constructed models, confirming some factors influencing teachers' digital teaching competence, such as attitude (Scherer et al 2019;Huang and Liaw, 2005), skills (Guillén-Gámez et al 2023;Kaarakainen et al 2018;Knezek and Christensen, 2016), gender, age (He et al 2023) and so on. Therefore, we focused on exploring the endogenous factors, including attitude and skills, combined with data literacy, which is rarely explored in prior studies but proven to be necessary for teachers.…”
Section: Discussionmentioning
confidence: 60%
“…Con el propósito de medir las competencias digitales del profesorado en labores de investigación, fue utilizado el instrumento elaborado por Guillén-Gámez et al (2023). Ello estaba compuesto por un total de 7 dimensiones a través de un modelo causal: D1habilidades digitales para buscar información, gestionarla, analizarla y comunicar los resultados; D2-Ética digital en investigación digital; D3-Flow Digital en labores de investigación; D4-Ansiedad hacia el uso de recursos TIC para investigar; D5-Calidad de los recursos TIC relacionados con la investigación; D6-Intención de usar las TIC para labores de investigación; D7-Integración recursos TIC para investigar.…”
Section: Instrumentounclassified
“…In order to measure teachers' digital competences in research work, the instrument developed by the authors (Guillén-Gámez et al, 2023). This was composed of a total of 7 dimensions through a causal model: D1-Digital skills to search, manage, analyse and communicate the results; D2-Digital ethics in digital research; D3-Flow Digital in research work; D4-Anxiety about the use of ICT resources for research; D5-Quality and availability of ICT resources related to research; D6-Intention to use ICT for research work; D7-Integration of ICT resources for research.…”
Section: Instrumentmentioning
confidence: 99%
“…Among the many critical processes related to the use of digital educational technology (edtech), one area has emerged with relation to the digital competence of in-service teachers and pre-service teachers [5,7]. This is the ICT proficiency of teachers, which is now regarded as a critical factor in the likelihood of success of the digitalisation of education at different levels [8,9]. Teacher digital competence has now become as important as competence in the use of analogue teaching resources [10].…”
Section: Introductionmentioning
confidence: 99%